2015
DOI: 10.1016/j.joen.2015.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Progression of Periapical Lesions with Zoledronic Acid in Ovariectomized Rats

Abstract: The hypoestrogenic condition aggravates the progression of periapical lesions. ZOL therapy may help contain bone destruction of periapical lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
(23 reference statements)
4
16
0
4
Order By: Relevance
“…However, our study showed that PARL may not always be a good indicator for RCT in BP-users; in the presence of BPs, no PARL was detected despite prominent pulp exposure and the histological presence of inflammatory cells and osteoclasts (Fig.2 A ). Indeed, such reports were previously documented in other clinical and preclinical observations (23, 24). These findings imply that pulpal infection may be gone unnoticed during routine dental examination due to no radiographic lesions and that such conditions may be falsely classified as “spontaneous ONJ” or the “staging 0 ONJ.”…”
Section: Discussionsupporting
confidence: 63%
“…However, our study showed that PARL may not always be a good indicator for RCT in BP-users; in the presence of BPs, no PARL was detected despite prominent pulp exposure and the histological presence of inflammatory cells and osteoclasts (Fig.2 A ). Indeed, such reports were previously documented in other clinical and preclinical observations (23, 24). These findings imply that pulpal infection may be gone unnoticed during routine dental examination due to no radiographic lesions and that such conditions may be falsely classified as “spontaneous ONJ” or the “staging 0 ONJ.”…”
Section: Discussionsupporting
confidence: 63%
“…), bisphosphonates (Wayama et al . ), selective oestrogen receptor modulators (Gomes‐Filho et al . ) and cathepsin K inhibitors (Suzuki et al .…”
Section: Discussionmentioning
confidence: 99%
“…() and Wayama et al . () reported that the periapical region in OVX animals had a higher amount of TRAP‐positive cells compared to sham animals. Also, Xiong et al .…”
Section: Discussionmentioning
confidence: 97%
“…, Wayama et al . , Romualdo et al . ), leading to an increase in the expression of proinflammatory cytokines and matrix metalloproteinases (Romualdo et al .…”
Section: Introductionmentioning
confidence: 99%